Adults’ Readiness to Learn and Skill Acquisition and Use: An Analysis of PIAAC - M Cecil Smith; Amy D. Rose; Thomas J. Smith; Jovita M. Ross-Gordon (Adult Education Research Conference, 2015)
This study examined the relationship between adults’ readiness to learn (RtL) and skill acquisition and use in the US sample of the PIAAC. RtL showed significant effects on each of the observed skill use outcomes. It was the strongest predictor of reading and writing skill use at home.
Keywords: PIAAC; readiness-to-learn; literacy skills; numeracy skills; technology skills